Profiling of protein thiophosphorylation by Phos‐tag affinity electrophoresis: Evaluation of adenosine 5′‐O‐(3‐thiotriphosphate) as a phosphoryl donor in protein kinase reactions. Issue 6 (18th February 2014) - Kinoshita, Eiji; Kinoshita‐Kikuta, Emiko; Shiba, Akio; Edahiro, Keisuke; Inoue, Yuki; Yamamoto, Kaneyoshi; Yoshida, Myu; Koike, Tohru
Abstract : Adenosine 5′‐ O ‐(3‐thiotriphosphate) (ATPγS) has been widely used as a phosphoryl donor to trace protein kinase activities. However, the question remains whether particular kinases accept ATPγS as readily as they accept natural ATP. We investigated the characteristics of several kinase reactions in the presence of ATPγS by using Phos‐tag affinity electrophoresis. The Phos‐tag gel permitted quantitative analysis of thiophosphorylated proteins produced by kinase reactions in vitro and it identified differences in the efficiencies of utilization of ATPγS and ATP in these reactions. Using the method, we evaluated the utility of ATPγS as a phosphoryl donor in studies on bacterial two‐component systems. Histidine kinases accepted ATPγS as readily as they accepted ATP in autophosphorylation reactions. However, downstream phosphotransfer reactions with ATPγS were markedly slower than the corresponding reactions with ATP. In an analysis of the sluggish thiophosphate transfer, we found that detergent‐denatured thiophosphorylated histidine kinases gradually hydrolyzed at the P–N bond, even at neutral pH, during incubation for 24 h, whereas the native form of the thiophosphorylated enzymes were much more stable. Profiling of protein thiophosphorylation by using Phos‐tag affinity electrophoresis might provide new insights into the characteristics of various types of kinase reactions with ATPγS.